ANTROPOLOGIENS POTENS I ALER ETTER DEN PRIMITIVES DØD - Eriksen, Thomas Hylland (Tidsskriftet Antropologi, 1999)
Thomas Hylland Eriksen: Anthropology and the Death of the Primitive Although anthropologists for generations have studied complex societies, the disciplinary shift in focus from “traditional” to “modem” phenomena has not as yet penetrated anthropologists’ way of teaching and theorizing. Even if a majority of anthropologists now study people and places that are deeply interconnected with the rest of the world, the paradigmatic examples of anthropological research are still the classic ones, from Malinowski to Evans-Pritchard and Douglas. This is not necessarily due merely to conservatism in the discipline, but could also indicate that the study of what was at the time perceived as “radical Othemess”, localized to societies presumed to be static and isolated, was, if empirically misleading, then exceptionally fruitful in generating models and ideas pertaining to society and culture. A question discussed in the article is thus whether current work on globalization, networks, cultural creolization et cetera (in which the author himself is engaged), has the same Creative potential as the study of “primitive” society - or whether the very craft of anthropology depends on an image of “radical Othemess”.